Lactobacillus Regulates Caenorhabditis elegans Cell Signaling to Combat Salmonella Infection - Zhou, Mengzhou; Liu, Xiaozhen; Yu, Hai; Gong, Joshua (Frontiers in Immunology, 2021)
Salmonella Typhimurium DT104 infection causes the death of Caenorhabditis elegans, which can be prevented by certain Lactobacillus isolates. However, the molecular mechanism of the host response to the infection and protection is largely unclear. This study has investigated the life-span and gene expression of key components in cell signaling of the nematode, both the wild-type (WT) and mutants. The results indicated that the gene expression of daf-16 in the DAF/ insulin-like growth factor (DAF/IGF) pathway, ced-3 and ced-9 in the programmed cell death (PCD) pathway, lys-7, spp-1, and abf-3 for antimicrobial peptide production, and bar-1 for the production of other defensing molecules was all upregulated significantly when the WT was subjected to DT104 infection. On the contrary, the gene expression of tir-1, sek-1, and pmk-1 in the p38 mitogen-activated protein kinase (MAPK) pathway and clec-60, sod-3, and skn-1 for the production of other defensing molecules was significantly suppressed by DT104. Pretreatment of the worms with L. zeae LB1 significantly upregulated the expression of almost all the tested genes except for ced-3, ced-9, abf-2, age-1, and dbl-1 compared with the nematode infected with DT104 only. Mutants defective in the cell signaling or other defense molecules of C. elegans were either more susceptible (defective in nsy-1, sek-1, pmk-1, ced-3, ced-9, skn-1, or daf16) or more resistant (defective in age-1 or dbl-1) to DT104 infection than the WT except for the mutant defective in sod-3. Mutants defective in antimicrobial peptides (lys-7 or abf-3) were also more susceptible than the WT. In contrast, the mutant defective in spp-1 became more resistant. When all the mutants were pretreated with L. zeae LB1, five mutants that are defective in nsy-1, sek-1, pmk-1, abf-3, or lys-7 showed no response to the protection from LB1. These results suggest that L. zeae LB1 can regulate C. elegans cell signaling including the p38 MAPK pathway and downstream production of antimicrobial peptides and defense molecules to combat Salmonella infection.